Employee Motivational Factors and Job Satisfaction: A Conceptual Study - Hong Loong Ang; Suddin Lada; Kehui Wang (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The objective of this study is to examine the relationship between employee motivational factors and job satisfaction among pet shops in Shanghai, China. The fast economic and social progress in China, along with the rapid growth of urbanization, has led to a growing awareness of independence among residents of cities. As a result, there has been a significant increase in the number of individuals who prefer to keep pets to get emotional support. The rapid expansion of the pet industry in China may lead to job dissatisfaction among employees in this sector due to increased work demands and potential issues related to the treatment and welfare of pets, which can be emotionally challenging. Therefore, this paper attempts to explore the influence of motivational factors on job satisfaction among employees of pet shops in Shanghai, China. Some of the issues being highlighted in the literature previously associated with the pet industry in China are related to antiquated motivational factors, conventional pet shop management, job dissatisfaction, and inefficiency of human resource management. Thus, this paper will discuss the main problems faced by pet shops in Shanghai related to motivational factors in their human resource practices and management.